Are tropical oceanic islands overlooked? Knowledge gaps regarding the vulnerability of amphibians to global anthropogenic threats - Renoir J. Auguste; Amy E. Deacon; Mark F. Hulme (Oryx)
Climate and land-use changes are major threats to amphibian conservation. However, amphibians on tropical oceanic islands appear to have been overlooked with regards to their vulnerability to global anthropogenic threats. Here we examine whether there are gaps in research evaluating the vulnerability of tropical oceanic island amphibians to climate and land-use changes. We carried out a systematic review of the literature on experimental studies published during 1 July 1998–30 June 2022, to evaluate whether there are knowledge gaps in relation to geographical scope, taxonomic representation, life stage assessment, the factors affecting amphibians and how species and populations respond to these factors. Of 327 articles on climate change and 451 on land-use change, the research of only 18 was carried out on tropical oceanic islands, only on anurans, and < 20% of the authors were affiliated with an oceanic island institution. These 18 studies were on only five islands, and the range of families and life stages assessed was limited. We also found uneven research into the factors affecting oceanic island amphibians and their responses; analyses involving the effect of temperature on amphibian range expansion or contraction were the most common, with few studies of the effects of salinity. The scarcity and unevenness of research from oceanic islands limit our understanding of the effects of climate and land-use changes on amphibians. We discuss potential reasons for these knowledge gaps and recommend ways to address them, such as more equitable distribution of resources and provision of training and research opportunities for island-based biologists.